Fear of Missing Out: A Scale Development with Focus on Hallyu Phenomenon - Ignatius Hari Santoso; Suzy Widyasari; Euis Soliha (Soegijapranata Catholic University, 2024)
Hallyu that is marked by the proliferation of entering South Korean culture into Indonesia has become a phenomenon for especially young Indonesian people. This culture includes Korean films and dramas, Korean music and songs, as well as the use of South Korean artists as brand ambassadors for local products. The influence of South Korean culture thoughtfully results in psychological changes of the generation Z in Indonesia especially those who are in the development from adolescence to adulthood. The purpose of this research is to develop a measurement scale on the aspects that are considered to have a significant influence on the psychological condition of fear of being outdated in young women of the generation Z in Indonesia. This research started by looking for the results of relevant studies. Upon the collection of the references, items that were tested for validity and reliability were formulated. The pre-test was conducted by involving 50 young women of the generation Z in Indonesia. After being declared valid and reliable, further tests was conducted to find indicators that have high loading factor values by involving 100 respondents. The study results in three constructs comprising interest on the Korean culture, social circle acceptance, and intention to consume Korean cultural products. Business people can use the questionnaire for increasing the sales figure.